KERUSAKAN EKOSISTEM MANGROVE DI KECAMATAN UJUNG PANGKAH KABUPATEN GRESIK PROVINSI JAWA TIMUR Degradation of Mangrove Ecosystem in Ujung Pangkah Subdistrict Gresik District East Java Province - Arif Prasetyo; Nyoto Santoso; Lilik Budi Prasetyo (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
The mangrove ecosystem in Ujung Pangkah Sub-district Gresik District has an important role in living life in the delta of Bengawan Solo River. The existence of mangrove ecosystem in this sub-district is threatened by land conversion activity, especially land conversion of mangrove forest to fishpond. In addition, sedimentation activities in the Solo River led to the formation of new land in the mouth of the river that formed the mudflat. This location is an important habitat for flora and fauna. The existence of mangrove forests and emerging lands is threatened by land conversion activities into ponds. The degradation condition of mangrove ecosystem in this research is coastal change in the form of abrasion and reduction of mangrove forest area determined by spatial approach with Geographic Information System application and remote sensing. Damage to mangrove ecosystem in the period 2006 to 2016 in the form of abrasion is 177.64 hectares, while the reduction of mangrove forest area in the same period of 101.70 hectares.Key words: Geographic Information System, remote sensing, Gresik, Bengawan Solo River